Standards of Medical Care in Diabetes—2013 (Diabetes care, 2013)
Strategies such as explicit goal setting with patients (504); identifying and addressing language, numeracy, or cultural barriers to care (505-508); integrating evidence-based guidelines and clinical information tools into the process of care (509-5 11); and incorporating care management teams including nurses, pharmacists, and other providers (512-515) have each been shown to optimize provider and team behavior and thereby catalyze reduction in A1C, blood pressure, and LDL cholesterol. Support patient behavior change Successful diabetes care requires a systematic approach to supporting patients' behavior change efforts, including a) healthy lifestyle changes (physical activity, healthy eating, nonuse of tobacco, weight management, effective coping), b) disease self-management (medication taking and management; self-monitoring of glucose and blood pressure when clinically appropriate), and c) prevention of diabetes complications (self-monitoring of foot health; active participation in screening for eye, foot, and renal complications; immunizations).